Plasma proteomics identifies a 'chemokine storm' in idiopathic multicentric Castleman disease. Issue 7 (16th May 2018) - Pierson, Sheila K.; Stonestrom, Aaron J.; Shilling, Dustin; Ruth, Jason; Nabel, Christopher S.; Singh, Amrit; Ren, Yue; Stone, Katie; Li, Hongzhe; van Rhee, Frits; Fajgenbaum, David C.
Abstract : Human Herpesvirus‐8 (HHV‐8)‐negative/idiopathic multicentric Castleman disease (iMCD) is a poorly understood disease involving polyclonal lymphoproliferation with dysmorphic germinal centers, constitutional symptoms, and multi‐organ failure. Patients can experience thrombocytopenia, anasarca, reticulin fibrosis, renal dysfunction, organomegaly, and normal immunoglobulin levels, – iMCD‐TAFRO. Others experience thrombocytosis, milder effusions, and hypergammaglobulinemia, –iMCD‐Not Otherwise Specified (iMCD‐NOS). Though the etiology is unknown in both subtypes, iMCD symptoms and disease progression are believed to be driven by a cytokine storm, often including interleukin‐6 (IL‐6). However, approximately two‐thirds of patients do not respond to anti‐IL‐6 therapy; alternative drivers and signaling pathways are not known for anti‐IL‐6 nonresponders. To identify potential mediators of iMCD pathogenesis, we quantified 1129 proteins in 13 plasma samples from six iMCD patients during flare and remission. The acute phase reactant NPS‐PLA2 was the only significantly increased protein ( P = .017); chemokines and complement were significantly enriched pathways. Chemokines represented the greatest proportion of upregulated cytokines, suggesting that iMCD involves a chemokine storm. The chemokine CXCL13, which is essential in homing B cells to germinal centers, was the most upregulated cytokine across all patients (log2 fold‐change = 3.22). Expression of CXCL13 was also significantly increased in iMCD lymph node germinal centers compared to controls in a stromal meshwork pattern. We observed distinct proteomic profiles between the two iMCD‐TAFRO patients, who both failed anti‐IL‐6‐therapy, and the four iMCD‐NOS patients, in whom all three treated with anti‐IL‐6‐therapy responded, suggesting that differing mechanisms may exist. This study reveals proteomic differences between flare and remission and the potential to molecularly define iMCD subgroups.